Journalism and media education in Nepal: A critical overview - Pant, Laxman Datt (Bodhi: An Interdisciplinary Journal, 2010)
This article explores the relevance of journalism education in Nepal based on personal observations of university teaching-learning practices. In particular, I focus on the triangular relationship between corporate, educational socioeconomic challenges of journalism/media education. I also analyze the recent trend of journalism and mass communication education in Nepal shedding light on the challenges of Nepalese media education system especially in the university level. I further suggest how media educators help determine what news is (not), and at the same time describe avenues for engaging media educators, policy makers and content producers for meeting the market demands. DOI: 10.3126/bodhi.v3i1.2809 Bodhi Vol.3(1) 2009 p.21-34